Popular justice: a history of lynching in America - Berg, Manfred (Dee, 2011)
The roots of lynching in Colonial and Revolutionary North America -- The rising of lynch law in Antebellum America -- Frontier justice -- Lynching, riots, and political terror in the Civil War years -- "Indescribable barbarism": the lynching of African Americans in the age of Jim Crow -- Popular justice beyond black and white -- The struggle against lynching -- From lynching to hate crime -- Lynching in American memory and culture
Includes bibliogr. references and index
Keywords: Geschichte; Lynchjustiz; USA